Modelling and calibration of credit-risky bonds - Spencer, Hewick Geoffrey (2008)
This thesis examines the corporate bond market in Japan during 1996-2001. The objective is to collect data, test and analyze the predictive ability of the Jarrow, Lando and Turnbull proposed Markov model for the term structure of credit risky spreads with the Kijima - Komorobayashi adjustment, in the determination of default probability within the Japanese market. We also examine the robustness and sensitivity of the results with respect to changes in recovery rates and spot interest rates.